Prevalence of postpartum post-traumatic stress disorder and associated factors among postnatal mothers in West Arsi zone, South West Ethiopia, 2024: a community-based cross-sectional study - Alemu, Solomon Seyife; Jarso, Mohammedamin Hajure; Gejo, Negeso Gebeyehu; Hebo, Habtemu Jarso; Bedecha, Daniel Yohannes; Bekele, Firomsa; Gezimu, Wubishet; Demsash, Addisalem Workie; Teferi, Sheleme Mengistu; Kitil, Gemeda Wakgari; Dube, Geleta Nenko; Yimer, Awol Arega; et al. (Frontiers in Psychiatry, 2024)
Background: Globally, up to one-third of women experience giving birth as traumatic, which can lead to postpartum post-traumatic stress disorder. Postpartum post-traumatic stress disorders have significant health consequences for the mother, child, and other family members. Although it has tragic health impacts, little is known about this problem in the study area. Objectives: The study aimed to assess the prevalence of postpartum posttraumatic stress disorder and associated factors among postnatal mothers. Methods: A community-based cross-sectional study was employed among 635 mothers in the first year after childbirth by using simple random sampling techniques from March 20 to April 20, 2024, in West Arsi Zone, Ethiopia. Face-to-face interviewers administered structured questionnaires used to collect the data. The collected data were cleaned, coded, and entered into Epidata and exported to Statistical Package for Social Sciences for further analysis. The collected data were cleaned, coded, and entered into Epidata . version 3.1software. Finally, the data were exported to Statistical Package for Social Sciences (SPSS) version 26 software for further analysis. Both bivariate and multivariable analyses were done by using binary logistic regression.A p-value of < 0.05 at 95% CI was used to determine significantly associated factors.Result: Of 635, 624 postnatal mothers participated in the study, for a response rate of 98.27%.The prevalence of postpartum post-traumatic stress disorder was 21.60% (95% CI: 18.40%, 24.87%).